2003
DOI: 10.1099/jmm.0.04966-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extended-spectrum β-lactamase-producing Gram-negative bacteria in septicaemic neonates in a tertiary care hospital

Abstract: The present study was undertaken to investigate the high incidence of multiresistant Gram-negative bacilli causing neonatal septicaemia. Samples of neonatal blood from 728 suspected cases were obtained in brain heart infusion broth with sodium polyanethol sulfonate. All Gram-negative rods isolated were subsequently subjected to routine antimicrobial susceptibility testing and tests for extended-spectrum â-lactamase (ESBL) production, as per NCCLS recommendations. ESBL was detected in 86·6 % of Klebsiella spp.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
80
4
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 24 publications
21
80
4
1
Order By: Relevance
“…Such high rate of ESBL among K. pneumoniae might be due to inappropriate use of antibiotics and self-medication against K. pneumoniae infection. However, our results are significantly better for ESBL producing K. pneumoniae than found by Afifi (2013) in Egypt (56.25%), Jain et al (2003) in India (86.6%) and Ullah et al (2009) in Pakistan (58.5%) (1,16,37).…”
Section: Discussioncontrasting
confidence: 54%
“…Such high rate of ESBL among K. pneumoniae might be due to inappropriate use of antibiotics and self-medication against K. pneumoniae infection. However, our results are significantly better for ESBL producing K. pneumoniae than found by Afifi (2013) in Egypt (56.25%), Jain et al (2003) in India (86.6%) and Ullah et al (2009) in Pakistan (58.5%) (1,16,37).…”
Section: Discussioncontrasting
confidence: 54%
“…Patient to patient transfer of ESBL producing strains of Klebsiella spp. could also be another reason as has been shown by Jain et al [21] in their study. In our study the prevalence of E. coli was observed to be 62 % which was in accordance with studies conducted by Shivprakasha et al (62.34%) [18] , and Gupta et al (63.79%) [19] .…”
Section: Discussionmentioning
confidence: 63%
“…The incidence of ESBL in major hospitals of India has been reported to be as high as 58% 19 . The range of ESBL isolation rate has been varied from 6 to 39% in different studies 20,21,22,23 25,26 was reported. The high incidence of ESBLs among E. coli may be peculiar to the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 99%